МЕТОД ФОРМИРОВАНИЯ МОЩНЫХ РАЗРЯДНЫХ ИМПУЛЬСОВ С ПОВЫШЕННОЙ СКОРОСТЬЮ НАРАСТАНИЯ ТОКОВ В НАГРУЗКЕ - Супруновская, Н.И. (Інститут електродинаміки НАН України, Київ, 2012)
The transient processes of storage capacitor discharge on the load at pulse current limiting in it using a fully controllable switch are studied. The method for increasing of rate of current rise in the load due to increasing the capacitance of the discharging capacitor is proposed. It is shown that at capacitor discharges on electro-spark load, which is characterized electrical resistance increasing with decreasing current in its, the dynamic losses in this switch are reduced. References 2.